Prevalence, awareness, treatment, and risk factor control of high atherosclerotic cardiovascular disease risk in Guangzhou, China - Liu, Hui; Lin, Weiquan; Tu, Kexin; Zhou, Qin; Wang, Chang; Sun, Minying; Li, Yaohui; Liu, Xiangyi; Lin, Guozhen; Li, Sidong; Bao, Wei (Frontiers in Cardiovascular Medicine, 2023)
Background: Identifying individuals at high risk of atherosclerotic cardiovascular disease (ASCVD) and implementing targeted prevention strategies might be the key to reducing the heavy disease burden in China. This study aimed to evaluate the prevalence, awareness, treatment, and risk factor control among individuals with high 10-year ASCVD risk in Guangzhou, China. Methods: This study included 15,165 adults (aged 18 years and older) from 138 urban and rural communities in the 2018 survey of China Chronic Disease and Risk Factors Surveillance in Guangzhou. 10-year ASCVD risk was estimated using the risk assessment models recommended in the Chinese Guideline for the Prevention of Cardiovascular Disease 2017. The prevalence, awareness, treatment, and risk factor control of high ASCVD risk (defined as 10-year risk≥10%) were examined. Results: Among the study population, the weighted proportion of men was 51.9%, and the mean age was 41.27±0.52 years. The overall standardized prevalence of high 10-year ASCVD risk was 13.8% (95% CI, 12.4%-15.3%). The awareness rates for hypertension, diabetes, and hyperlipidemia were 48.0% (95% CI, 42.8%-53.4%), 48.3% (95% CI, 43.0%-53.7%), and 17.9% (95% CI, 14.4%-22.1%) among those with corresponding risk factors. The proportions of drug use in prevention were relatively low in primary prevention, with the rates of using BP-lowering, glucose-lowering, lipid-lowering, and aspirin being 37.7% (95% CI, 32.8%-42.8%), 41.4% (95% CI, 35.8%-47.3%), 6.7% (95% CI, 4.5%-10.0%), and 1.0% (95% CI, 0.6%-1.8%), respectively. As for risk factor control, only 29.3% (95% CI, 25.7%-33.2%), 16.8% (95% CI, 15.0%-18.6%), and 36.0% (95% CI, 31.1%-41.2%) of individuals with high ASCVD risk had ideal levels of blood pressure, LDL-C, and body weight. Conclusion: The estimated prevalence of 10-year high ASCVD risk was high in Guangzhou, while the rates of treatment and risk factor control in primary prevention were still far from optimal, especially for lipid management. These findings suggested that substantial improvement in ASCVD prevention is needed in this population.